The constitutional-legal status of the Spiritual Association of Muslims of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
This article describes the constitutional-legal status of «The Spiritual Association of Muslims of Kazakhstan» (SAMK), is headed by the chief Mufti. The author in a research especially paid attention to the interaction of State and the SAMK in the history of the Kazakhstan and also considers one of possibilities of its development. Author finds it necessary to increase legal personality of «The Spiritual Association of Muslims of Kazakhstan» for strengthening religious and national security of Kazakhstan.Key words: Spiritual Administration of Muslims of Kazakhstan, islam, the legal status, state and religious relations, religious association, Hanafi school.